Is Fetal Endoscopic Tracheal Occlusion (FETO) a Predisposing Factor for Acid Gastro-Esophageal Reflux in Infants With Congenital Diaphragmatic Hernia? - Macchini, Francesco; Morandi, Anna; Mazzoleni, Stefano; Ichino, Martina; Cavallaro, Giacomo; Raffaeli, Genny; Ferrari, Carlo; Gangi, Silvana; Mosca, Fabio; Fabietti, Isabella; Persico, Nicola; Leva, Ernesto (Frontiers in Pediatrics, 2020)
Introduction - various anatomical defects predispose patients with congenital diaphragmatic hernia (CDH) to develope Gastro-Esophageal Reflux Disease (GERD). The Fetal Endoscopic Tracheal Occlusion (FETO) has increased the survival of severe CDHs. Aim of this study was to study GERD in patients that underwent FETO. Materials and Methods - We included patients with CDH treated with or without FETO (“FETO” and “no-FETO” group, respectively) from 2013 to 2016. Data on Gestational Age (GA), Birth Weight (BW), initial Observed/Expected Lung to Head Ratio (O/E LHR), final O/E LHR, duration of ventilation and hospitalization, maximal tracheal diameter and pulmonary volume were collected. All patients underwent pH-metry after 1 year of life, and the results were compared between groups and correlated to risk factors. Results - Thirty-two patients were included in the study: 10 FETO, 22 no-FETO. No significant differences were observed in pH-metries of the two groups. No correlation was found between GA, BW, initial O/E LHR, maximal tracheal diameter, pulmonary volume and pH-metric results. PH-metries correlated with total duration of ventilation (R=0.5, p=0.003) and of hospitalization (R=0.54, p=0.001). Gastric herniation is associated with worse pH-metry. Conclusion -FETO procedure does not seem to represent an independent risk factor for GERD. However, the most severe CDH have worst GERD.